POPULASI LARVA Oryctes rhinoceros (COLEOPTERA : SCARABAEIDAE) PADA BEBERAPA JENIS MEDIA PENELURAN DI PERKEBUNAN KELAPA KECAMATAN MAPANGET KOTA MANADO - Alfiando A. Sasauw; Jusuf Manueke; Dantje Tarore (COCOS, 2017)
ABSTRACT This study aims to determine how the impact media coconut powder combination of cow dung and sawdust combination of cow manure on a rhinoceros beetle (Oryctes rhinoceros) in the process of laying eggs to become larvae, the study was conducted on a coconut plantation village courts Subdistrict Mapanget Manado City. Research using randomized complete block design (RAK) with 6 treatments and 5 replicates, as the treatment is treatment A, 5 kg coconut powder mixed with 1 kg of cow dung, treatment B, 5 kg coconut powder mixed with 2 kg of cow dung, treatment C, 5 kg coconut powder mixed with 3 kg of cow dung, treatment D, 5 kg of sawdust mixed with 1 kg of cow dung, treatment E, 5 kg of sawdust mixed with 2 kg of cow dung, treatment F, 5 kg of sawdust mixed with 3kg dirt cow. This treatment can be seen from where the nesting media most preferred by pest O. rhinoceros in doing laying up into larvae.Â  The results showed that coconut powder media with a combination of cow dung is preferred by O. rhinoceros pests to multiply compared with sawdust with a combination of cow dung, larval populations obtained in the treatment of cow dung combination of coconut powder reached 2.98% (42 larvae) and the treatment of the combination of cow manure sawdust reached only 0.71% (no larval populations). Keywords: Coconut powder, sawdust, Oryctes rhinoceros